2020
DOI: 10.1002/aqc.3444
|View full text |Cite
|
Sign up to set email alerts
|

Designing environmental DNA surveys in complex aquatic systems: Backpack sampling for rare amphibians in Sierra Nevada meadows

Abstract: 1. Surveys for environmental DNA (eDNA) can provide an efficient and effective means of detecting aquatic organisms in various types of aquatic systems. 2. In the summer of 2017, the efficacy of a new, integrated eDNA backpack sampler to detect two native amphibians (Rana sierrae and R. cascadae) at risk was tested in complex mountain meadows in California. Samples were collected at 65 locations in 15 meadows where the target species were known to be present or were historically present. 3. Collection and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…First, we found that both metabarcoding and qPCR improved the detection of two imperiled amphibians, beyond the best available field methods. For monitoring programs where rare species are the primary focus (Table 1), eDNA methods alone might provide more information and entail less disturbance than conventional surveys (Pope et al, 2020). In addition to improving amphibian detection, eDNA analysis of a single sample using qPCR and metabarcoding can provide data on some of the most pressing threats for amphibians: disease (Huver et al, 2015; Kamoroff & Goldberg, 2017), hybridization (Stewart & Taylor, 2020), and non‐native species (Dejean et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we found that both metabarcoding and qPCR improved the detection of two imperiled amphibians, beyond the best available field methods. For monitoring programs where rare species are the primary focus (Table 1), eDNA methods alone might provide more information and entail less disturbance than conventional surveys (Pope et al, 2020). In addition to improving amphibian detection, eDNA analysis of a single sample using qPCR and metabarcoding can provide data on some of the most pressing threats for amphibians: disease (Huver et al, 2015; Kamoroff & Goldberg, 2017), hybridization (Stewart & Taylor, 2020), and non‐native species (Dejean et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Species‐specific eDNA approaches commonly use quantitative PCR (qPCR), in which DNA from a single target species is amplified with primers and, increasingly, a probe specific to that species. Owing to their highly sensitive and specific nature, qPCR assays are a powerful tool for monitoring cryptic or low‐density taxa, for example, endangered species (Biggs et al, 2015; Katz et al, 2021; Pope et al, 2020; Schmelzle & Kinziger, 2016) and non‐native species in the early stages of invasions (Larson et al, 2020; Takahara et al, 2013; Tingley et al, 2019). qPCR is also relatively low‐cost and rapid, in some cases, even allowing real‐time species detection in the field (Thomas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…1). Use of the Smith-Root eDNA sampler has been reported in the previous scientific literature (Thomas et al 2018(Thomas et al , 2019(Thomas et al , 2020Gasparini et al 2020;Pope et al 2020;Skinner et al 2020) while the use of the Halltech, to the authors' best knowledge, has not.…”
Section: Introductionmentioning
confidence: 93%
“…Many methodological approaches have been developed for collecting and processing eDNA samples, including portable technology that allows processing eDNA samples on-site, though this has resulted in a lack of standardized methods for eDNA sampling. One commercially available eDNA sampler is the portable filtration system developed by Smith-Root (Thomas et al 2018;Smith-Root 2020) which has been widely used (Thomas et al 2018(Thomas et al , 2020Skinner et al 2020;Pope et al 2020;Loeza-Quintana et al 2021). To inform best practices surrounding eDNA collection, the second objective of this study compared two eDNA portable filtration systems: the Smith-Root eDNA sampler (Thomas et al 2018;Smith-Root 2020), and the OSMOS eDNA sampler from Halltech Aquatic (Halltech 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sampling of eDNA is straightforward and can be facilitated by instructional videos together with detailed and illustrated instructions (Agersnap et al, 2022) and supported by sampling gear that is easy to carry around (e.g., Pope et al, 2020). Posting filters preserved with 2 mL ethanol with regular postal service, might not be possible in other countries, but the ethanol can easily be replaced by a nonflammable buffer solution.…”
Section: Benefits and Challenges Of Citizen Science In Edna Researchmentioning
confidence: 99%